Myocardial perfusion imaging pattern in patients with intermediate and significant coronary artery stenosis; European Journal of Nuclear Medicine and Molecular Imaging; Vol. 42, suppl. 1: European Association of Nuclear Medicine, EANM'15 - Zavadovsky K. V. Konstantin Valerievich; Gulya M. O. Marina Olegovna; Saushkin V. V. Viktor Vyacheslavovich; Saushkina Yu. V. Yuliya Vyacheslavovna; Lishmanov Yu. B. Yury Borisovich (2015, 2015)
Title screen